REORIENTASI PERAN BIROKRASI DALAM MENINGKATKAN PROFESIONALITAS PELAYANAN PUBLIK - F. Winami, F. Winami (Jurnal Cakrawala Pendidikan, 2016)
Social reality shows that the i~npressiona bout the performance of the bureaucracy is that it is rigid. centralized. untouched by change, and inefficient. However. the present era ofeconomic and informational globalization and the rapid development of science, technology, and art demand that there are also changes in the administration system that suppol-ts the bureaucracy. Therefore, there needs to be a reorientation of the bureaucracy to make it more creative. The changes in need of attention are, among others. 1. the changes of the form and structure of the bureaucracy which are stable-mechanical into those which are organicadaptable, 2. the changes of the principles producing classic management into those producing new public management, and 3. the changes in the form of decentralization/ redistribution of power to the people to encourage their heightened pasticipation in all aspects of development. The university as an agent of reformation and producer of quality bureaucrats also has to change to be synchronous with the attempted changes above. Therefore, changes in the curriculum need to be made to make it more adaptable and a university managerial system that stimulates creative attitude needs to be adopted and developed.